Impact of a nature-based intervention on incarcerated women. Issue 4 (17th December 2018) - Toews, Barb; Wagenfeld, Amy; Stevens, Julie
Abstract : Purpose: The purpose of this paper is to understand the impact of a short-term nature-based intervention on the social-emotional well-being of women incarcerated on a mental health unit in a state prison. Design/methodology/approach: This research used a mixed method approach with individual interviews, a focus group and a visual analog scale (VAS). Findings: Qualitative results found that women appreciated the planting party and the way the plants improved the physical environment. Women were also emotionally and relationally impacted by their participation and practiced skills related to planting and working with people. Quantitative results indicate that women were happier, calmer, and more peaceful after the intervention than before. Research limitations/implications: Study limitations include sample size, self-report data and use of a scale not yet tested for reliability and validity. Practical implications: Findings suggest that nature-based interventions can serve as an adjunct to traditional mental health therapies in correctional settings. Nature-based interventions can support women's goals to improve their mental health. Social implications: Findings suggest that nature-based interventions can serve to improve relationships among incarcerated women, which may make a positive impact on the prison community. Such interventions may also assist them in developing relational and technical skills that are useful upon release. Originality/value: To date, there is limited knowledge about the impact of nature-based interventions on incarcerated individuals coping with mental health concerns.